PERENCANAAN EKONOMI DALAM PERSPEKTIF ISLAM - Imam, Muhammad Aniq (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractEconomic planning, the process by which key economic decisions are made or influenced by central governments. It contrasts with the laissez-faire approach that, in its purest form, eschews any attempt to guide the economy, relying instead on market forces to determine the speed, direction, and nature of economic evolution. By the late 1960s the majority of the worldâs countries conducted their economic affairs within the framework of a national economic plan. Economic planning refers to any directing or planning of economic activity outside the mechanisms of theÂ market.Â PlanningÂ is anÂ economic mechanismÂ for resource allocation and decision-making held in contrast with the market mechanism, where planning refers to a direct allocation of resources. Most economies are mixed economies, incorporatingÂ elements of marketsÂ andÂ planningÂ for distributingÂ inputsÂ and outputs. The level of centralization of decision-making in the planning process ultimatelyÂ dependsÂ onÂ theÂ typeÂ of planningÂ mechanismÂ employed; as such planning need not be centralized and may be based on either centralized or decentralized decision-making. Economic planning can apply to production, investment, distributionÂ or all three of these functions. Planning may take the form of directive planning or indicative planning. An economy primarily based on central planning is a planned economy; in a planned economy the allocation of resources is determined by a comprehensive plan of production which specifies output requirements. The Economic planning in Quranic perspective has faith and moral oriented as mentioned in Yusuf story in Holy Quran.Kata Kunci:Â perencanaan ekonomi, ekonomi Islam, sistem Islam, Nabi Yusuf